2022
DOI: 10.3390/rs14184556
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Surface Deposits in the Balmer-Kapteyn Cryptomare Region Provided by Chang’E-2 Microwave Radiometer Data

Abstract: Lunar cryptomare records both early-stage mare volcanisms and large-scale impact cratering, which can provide important information about the thermal evolution of the Moon. We built a mixing dielectric constant model to represent the cryptomare deposits mixed by highland debris and mare deposits, and the proper radiative transfer simulation was constructed to evaluate the thermal emission features of surface deposits in the cryptomare region. The microwave radiometer (MRM) data in the Balmer-Kapteyn region wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…> < 2 [3], [4], [13], [17], [18] using MRM data. The thermal emission properties of surface deposits in the B-K cryptomare region were assessed by Tang et al [15]. These results demonstrate the special use of MRM data in comprehending lunar surface deposits.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…> < 2 [3], [4], [13], [17], [18] using MRM data. The thermal emission properties of surface deposits in the B-K cryptomare region were assessed by Tang et al [15]. These results demonstrate the special use of MRM data in comprehending lunar surface deposits.…”
mentioning
confidence: 83%
“…It has been shown that MRM data are sensitive to substrate regolith temperature at different depths, compositions, and thermal emission features. These information provide a thorough explanation of surface deposits in a vertical direction [4], [12][13][14][15][16]. The microwave thermal emission properties of mare deposits in Moscoviense Basin and Mare Australe, mare units in Rümker, and surface deposits in Tsiolkovskiy crater were assessed by Meng et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of ejecta deposition from large craters would have occurred concurrently with basalt emplacement 34 , potentially affecting the lling of the basins. Furthermore, studies utilizing data from the Chang'E-2 microwave radiometer and groundbased radar 12,13 have provided insights into the shallow subsurface of the cryptomaria. Compared to spectral data, these techniques have the advantage of detecting deeper information, to infer the boundary between the upper ejecta of the cryptomaria and the lower mare basalts.…”
Section: Cryptomaria Thicknessmentioning
confidence: 99%
“…Accurate mapping of the mineral composition of the lunar surface is crucial for understanding the thermal evolution of the Moon and the formation of its mare and mascons [1,2]. However, the presence of nanophase iron (np-Fe 0 ) particles resulting from space weathering, as well as the lunar soil cover, introduce significant uncertainties in the retrieval of the lunar surface mineral composition using multispectral remote sensing data [3].…”
Section: Introductionmentioning
confidence: 99%